Farmers’ preferences and willingness to pay for traits of sorghum varieties: Informing product development and breeding programs in Tanzania - Miriti, Philip; Regassa, Mekdim D.; Ojiewo, Christopher Ochieng; Melesse, Mequanint B. (Informa UK Limited, 2023)
Smallholder farmers’ decisions to adopt improved varieties are expected to be critically governed by their preferences and willingness to pay for different traits of these varieties. This study examined farmers’ preferences for sorghum (Sorghum bicolor (L.) Moench) variety attributes and estimated their willingness to pay (WTP) for these attributes using choice experiment data from >1,300 sorghum farmers in Tanzania. Empirical findings showed that farmers had strong preferences for sorghum varieties that were tolerant to environmental stresses, high yielding, early maturing, fetching higher grain prices, and white in color. Significant heterogeneity was observed in farmers’ preferences across various traits. The WTP estimates revealed that farmers were willing to pay the highest premium for tolerance to environmental stresses, amounting, on average, to three times higher than the WTP for other traits. Our results have important implications for demand-driven variety development that could contribute to improving crop productivity and household welfare.